The Bible in the Bush: The First "Literate" Batswana Bible Readers (translation. a transdisciplinary journal, 2022)
In this article I begin with Laura Bohannan's 1966 celebrated essay "Shakespeare in the Bush;' which is where I derive the title "The Bible in the Bush." I then discuss some of the first written responses of Batswana to Robert Moffat's translation of the Setswana Bible of 1857. The third and final part of the article looks at some implications for biblical translations in the context of globalization and localization.